THE INFLUENCE OF PUBLIC PERCEPTION OF BPJS EMPLOYMENT ON DECISION MAKING - Nur Ayu Resmara Tresna; Nina Siti Salmaniah Siregar; Patisina (RADJA PUBLIKA, 2025)
The aim of this study is to determine the influence of public perception on decision making.This study adopted a quantitative approach. The types of data used are primary and secondary data. Primary data from questionnaires. Secondary data were obtained from the annual report published by the Medan City Central Statistics Agency in 2023. The number of research samples was 400. The analysis was carried out through an approach using the Partial Least Square-Structural Equation Model (PLS-SEM). Public perception has a positive and significant effect on decision making to participate in social security in Medan City. Brand awareness has a positive and significant effect on decision making to participate in social security in Medan City. Public perception has a positive and significant effect on brand awareness regarding social security programs in Medan City. Brand awareness significantly mediates the influence between public perception on decision making to participate in social security in Medan City.